Central Metabolic Responses to Ozone and Herbivory Affect Photosynthesis and Stomatal Closure . Issue 3 (6th October 2016) - Papazian, Stefano; Khaling, Eliezer; Bonnet, Christelle; Lassueur, Steve; Reymond, Philippe; Moritz, Thomas; Blande, James D.; Albrectsen, Benedicte R.
Abstract : When confronted with sequential abiotic and biotic stress, black mustard regulates glycerol and central energy metabolism to prioritize processes of photosynthesis and stomatal osmoregulation. Abstract: Plants have evolved adaptive mechanisms that allow them to tolerate a continuous range of abiotic and biotic stressors. Tropospheric ozone (O3 ), a global anthropogenic pollutant, directly affects living organisms and ecosystems, including plant-herbivore interactions. In this study, we investigate the stress responses of Brassica nigra (wild black mustard) exposed consecutively to O3 and the specialist herbivore Pieris brassicae . Transcriptomics and metabolomics data were evaluated using multivariate, correlation, and network analyses for the O3 and herbivory responses. O3 stress symptoms resembled those of senescence and phosphate starvation, while a sequential shift from O3 to herbivory induced characteristic plant defense responses, including a decrease in central metabolism, induction of the jasmonic acid/ethylene pathways, and emission of volatiles. Omics network and pathway analyses predicted a link between glycerol and central energy metabolism that influences the osmotic stress response and stomatal closure. Further physiological measurements confirmed that while O3 stress inhibited photosynthesis and carbon assimilation, sequential herbivory counteracted the initial responses induced by O3, resulting in a phenotype similar to that observed after herbivory alone. This study clarifies the consequences of multiple stress interactions on a plant metabolic system and also illustrates how omics data can be integrated to generate new hypotheses in ecology and plant physiology.